Memahami Konsep Dasar Organisasi dan Manajemen - All Habsy, Bakhrudin; Dianing Armania, Selomita; Badriyahtus Sholikah, Erika; Hafizhah, Maryam; Putri Maharani, Alifia (Journal of Comprehensive Science, 2024)
Nowadays, organization and management are very important in almost every field of human life. Therefore, in order to live this life well, we should have understood the basic concepts of organization and management first. The purpose of this research is to be able to know and understand the basic concepts in organization and management in detail and clearly. The research method used is descriptive qualitative research method with literature study data collection technique. The results of this study include the basic concepts of organization, which are as follows: (1) definition, (2) purpose, (3) elements, and (4) types of organizations. In addition, the results of this study also include the basic concepts of management, namely as follows: (1) definition, (2) elements, (3) scope, (4) objectives, (5) functions, (6) processes, (7) general principles, along with (8) types in management. The conclusion of this research is that organization and management have a close relationship because management is an important element in the success of an organization.